SEMANTIC FIELD OF PHRASEOLOGICAL UNITS REFLECTING THE CULTURE OF THE RUSSIAN LANGUAGE: https://doi.org/10.5281/zenodo.15426795 - Abduzhalilov , Marufjon (Journal of Contemporary World Studies, 2025)
The article is devoted to the study of the semantic field of phraseological units reflecting the culture of the Russian language. The peculiarities of the semantics of phraseological units, their structure, and their role in conveying national specificity and mentality are considered. Special attention is paid to the theory of the semantic field as a tool for the analysis of phraseological material. The article analyses in detail the thematic block 'person', revealing universal and national specific features in the assessment of individual and social qualities of a person. The article shows how the portrait of the personality and the world view of the Russian ethnos are reflected by phraseological units.